Research methods in human skeletal biology - DiGangi, Elizabeth A.; Moore, Megan K. (Academic Press, 2013)
Research Methods in Human Skeletal Biology serves as the one location readers can go to not only learn how to conduct research in general, but how research is specifically conducted within human skeletal biology. It outlines the current types of research being conducted within each sub-specialty of skeletal biology, and gives the reader the tools to set up a research project in skeletal biology. It also suggests several ideas for potential projects. Each chapter has an inclusive bibliography, which can serve as a good jumpstart for project references. Provides a step-by-step guide to conducting research in human skeletal biology. Covers diverse topics (sexing, aging, stature and ancestry estimation) and new technologies (histology, medical imaging, and geometric morphometrics). Excellent accompaniment to existing forensic anthropology or osteology works.